O Comportamento Visual de Basquetebolistas sub14 em Jogos Reduzidos e Condicionados - João Pedro Ferreira Araújo (2018)
In this dissertation the visual search behavior of U14 basketball players in different competitive levels (such as national and regional) was evaluated during small-sided and conditioned games (i.e. 1vs1 and 2vs1), from the defensive point of view. A total of 48 male players (13,7 ± 0,7 years of age) were tested, 12 players (13,8 ± 0,8 years of age) were included in the national competition group and the remaining 36 athletes (13,7 ± 0,8 years) formed the regional group. The visual search behavior was recorded through the eye tracking system Tobbi Pro Glasses 2®, having used the following visual indicators: medium fixation duration, number of fixations per repetition, medium fixation duration per area of interest, number of fixations per area of interest and percentage of the time of fixation per area of interest. The obtained results showed significative statistical differences in the strategies of visual search among situations of 1vs1 and 2vs1, being the first situation characterized by a larger number of fixations than the second situation (7,223 ± 1,882 vs 6,517 ± 1829). Statistical evidence was also observed among both groups of different competitive levels. Regarding the situation of 1vs1, the group of national competition accomplished a larger number of fixations in the area of ball (National Group=1,113 ± 0,968; Regional group=0,661 ± 0,522) and area upper limb with the ball of the player in ball possession (National Group=0,992 ± 0,602; Regional Group=0,594 ± 0,462), also showing a higher percentage of time fixation for the same areas of interest (Ball: National Group=15,628 ± 14,310, Regional Group=8,342 ± 7,485; Upper limb with the ball of the player in ball possession: National Group=13,284 ± 9,812, Regional Group=7,567 ± 6,638) when compared with the group of regional competition. No differences were found for the 2vs1 situation among groups. By so, we can infer that youth basketball players showed different visual search behaviors according to the task and competitive level.